Strategi Pemanfaatan Perairan Pesisir untuk Budi Daya Kerang Hijau (Perna viridis L.) di Kuala Langsa, Provinsi Aceh - Andi Sagita; Rahmat Kurnia; . Sulistiono (Institut Pertanian Bogor, 2017)
Development of green mussel culture currently still requires the determination of strategies in accordance with the potential and conditions of coastal areas as well as management culture system. This research aims to formulate strategies of the utilization coastal waters for green mussel culture in coastal Kuala Langsa, Aceh Province. Data collected to identify internal factors and external, including primary and secondary data, while the determination of respondents using purposive sampling method. SWOT Analysis is used for strategy determined while prioritizing strategy using Quantitative Strategies Planning Matrix (QSPM) analysis. Based on SWOT analysis, identified 9 strength factors, 4 weakness factors, 6 opportunity factors, and 5 threat factors and 8 strategies, then the priority of strategies is determined with QSPM analysis, the sequence of the most important priority is: counseling and training to improve the management of green mussel culture for coastal communities (WO1); green mussel culture can be integrated with the involvement of coastal communities as stakeholders (WO2); optimization of coastal waters for green mussel culture is supported by ecology conditions (SO1); green mussel culture can be done with longline method with a density of 20 individuals/basket 5.30 l (SO3); site selection for culture and spat collection of green mussel should consider coastal oceanographic factors (ST1); controlling the level of waste disposal from the mainland so as not to pollute coastal areas (ST2); and to formulate practical guidance of management of green mussel culture based on the food security principle.